1992
DOI: 10.1042/bj2810407
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of insulin- and adaptive-regulation-induced system A activation to microtubular function in skeletal muscle

Abstract: 4071. Insulin and adaptive regulation are known to stimulate system A amino acid transport activity in skeletal muscle. The present study was designed to investigate whether activation of system A in muscle is a consequence of processes which rely on microtubule or microfilament function. To that end, extensor digitorum longus (EDL) muscles were incubated in the presence of colchicine and cytochalasin D, well-known inhibitors of microtubule and microfilament activity respectively. 2. Basal a-(methyl)aminoisobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Moreover, the magnitude of system ASC activity stimulation was sufficient to explain the increase in overall Lalanine transport observed following forskolin. Consistent with our results, studies performed in skeletal muscle and placental membranes have demonstrated that neither forskolin nor cholera toxin, both cAMP-elevating factors, affect system A activity (Guma et al, 1992;Pastor-Anglada et al, 1996). Likewise, results from trout hepatocytes have revealed that system ASC, but not system A, was rapidly stimulated by glucagon (Gallardo et al, 1996).…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, the magnitude of system ASC activity stimulation was sufficient to explain the increase in overall Lalanine transport observed following forskolin. Consistent with our results, studies performed in skeletal muscle and placental membranes have demonstrated that neither forskolin nor cholera toxin, both cAMP-elevating factors, affect system A activity (Guma et al, 1992;Pastor-Anglada et al, 1996). Likewise, results from trout hepatocytes have revealed that system ASC, but not system A, was rapidly stimulated by glucagon (Gallardo et al, 1996).…”
Section: Discussionsupporting
confidence: 80%
“…An interesting feature of insulin action is the evidence that most physiological situations associated with System A up-regulation in liver parenchymal cells are characterized either by insulin deficiency or by resistance to the hormone. Some examples are: diabetes [41][42][43] where skeletal muscle also shows increased System A activity [44], starvation [45][46][47], pregnancy [48,49], and post-natal development [50][51][52]. Insulin also down-regulates the liver System A activity of streptozotocin-induced diabetic rats, either when added to cells in culture or after administration in vivo [41,42].…”
Section: Specificity and Distribution Of Transport Systemsmentioning
confidence: 99%
“…System A upregulation in many cells required intact microtubules. For example, upregulation of system A transport in skeletal muscle in response to insulin or adaptation involves synthesis of new carriers and requires the integrity of microtubule function (53). Colchicine has also been found to prevent the increased capacity for system A transport in the proliferating hepatocytes during liver regeneration (54).…”
Section: Possible Role Of Microtubules and Protein Kinases For The Osmentioning
confidence: 99%